Aspirin for Primary Cardiovascular Prevention in Patients with Diabetes: Uncertainties and Opportunities - Del Bianco-Rondeau, Mélina; Robert-Halabi, Maxime; Bloom, Samara; Rabasa-Lhoret, Remi; Tardif, Jean-Claude; Lordkipanidzé, Marie; Marquis-Gravel, Guillaume (Thrombosis and Haemostasis, 2022)
The use of the antiplatelet agent aspirin (acetylsalicylic acid) was previously routinely recommended for the primary prevention of cardiovascular (CV) events in patients with diabetes, but recent large-scale randomized trials have failed to demonstrate a sizeable net clinical benefit with a once-daily, low-dose (81–100 mg) regimen in this population. Previous pharmacokinetic and pharmacodynamic studies have suggested that the aspirin formulation (enteric-coated) and dosing schedule (once daily) studied in randomized trials for primary prevention of CV events defining contemporary clinical practice may not leverage the full potential of the drug, particularly in patients with diabetes. Indeed, the diabetic platelets bear characteristics that increase their thrombotic potential and alter their pharmacologic response to the drug. Consequently, the appropriateness of studying a uniform aspirin regimen in landmark primary prevention trials needs to be revisited. In this review, we present the evidence showing that diabetes not only increases baseline platelet reactivity, but also alters platelet response to aspirin through different mechanisms including a faster platelet turnover rate. Obesity, which is frequently associated with diabetes, also impacts its pharmacokinetics via an increase in distribution volume. Small-scale pharmacokinetic and pharmacodynamic studies have suggested that the relative aspirin resistance phenotype observed in patients with diabetes may be reversed with a twice-daily dosing schedule, and with nonenteric-coated aspirin formulations. Properly powered randomized controlled trials investigating the efficacy and safety of aspirin dosing schedules and formulations tailored to the population of patients with diabetes are urgently required to optimize patient care.
Keywords: diabetes mellitus; aspirin resistance; aspirin; antiplatelet agent; platelet